Paraguay : 2017 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights that Paraguay has grown robustly despite a more challenging external environment. The economy gained momentum toward the end of 2016 and expanded by 6.5 percent (year-over-year) during the first quarter of 2017. Real GDP growth is projected to reach 4.2 percent in 2017, reflecting a more moderate pace of activity in the second half of the year. Investment will likely be a crucial driver of growth, as major infrastructure projects are undertaken. Over the medium term, real GDP growth is expected to remain near potential of just below 4 percent. Risks around the outlook are to the downside, especially from heightened political uncertainty in Brazil.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet